The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1164/ajrccm.162.2.9909099
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Surfactant Treatment of Meconium-induced Acute Lung Injury

Abstract: Substances (for example, serum proteins or meconium) that interfere with the activity of pulmonary surfactant in vitro may also be important in the pathogenesis or progression of acute lung injury. Addition of polymers such as dextran or polyethylene glycol (PEG) to surfactants prevents and reverses surfactant inactivation. The purpose of this study was to find out whether surfactant/polymer mixtures are more effective for treating one form of acute lung injury than is surfactant alone. Acute lung injury in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 26 publications
3
65
0
5
Order By: Relevance
“…The concentration of HA both in saline and in Survanta was 0.25% (wt/vol). The choice of 50 mg/kg Survanta was based on our previous studies of meconium lung injury in which we found that the addition of polyethylene glycol (PEG) to 50 mg/kg Survanta significantly improved measures of gas exchange and lung mechanics when compared with 50 mg/kg Survanta alone (15). We chose to use the same protocol with respect to injury model, surfactant, and dose as in the previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of HA both in saline and in Survanta was 0.25% (wt/vol). The choice of 50 mg/kg Survanta was based on our previous studies of meconium lung injury in which we found that the addition of polyethylene glycol (PEG) to 50 mg/kg Survanta significantly improved measures of gas exchange and lung mechanics when compared with 50 mg/kg Survanta alone (15). We chose to use the same protocol with respect to injury model, surfactant, and dose as in the previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Both in vitro (1)(2)(3)(4)(5)(6) and in vivo (7)(8)(9) trials have shown that these nonionic polymers can significantly improve the surface activity of different therapeutic lung surfactants and effectively reverse inactivation due to a variety of inhibitory substances.…”
mentioning
confidence: 99%
“…We and others have found that the addition of nonionic polymers [principally polyethylene glycol (PEG), or dextran] further reduces surfactant inactivation by serum, meconium, or other substances in vitro (10 -12). In vivo studies also demonstrate that the addition of nonionic polymers to therapeutic surfactants improves pulmonary function after lung injury caused by meconium, albumin, hydrochloric acid, milk acid, or endotoxin (11,(13)(14)(15)(16).The successful experiments with nonionic polymers led us to consider using ionic polymers. In this study, we investigated whether hyaluronan (HA) has effects on pulmonary surfactants that are similar to those described for dextran and PEG.…”
mentioning
confidence: 99%